2020
DOI: 10.3389/fcvm.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

Serum GDF15, a Promising Biomarker in Obese Patients Undergoing Heart Surgery

Abstract: Background: Obesity is a risk factor that negatively impacts outcomes in patients undergoing heart surgery by mechanisms that are not well-defined nor predicated on BMI alone. This knowledge gap has fuelled a search for biomarkers associated with cardiovascular diseases that could provide clinical insight to surgeons. One such biomarker is growth differentiation factor15(GDF15), associated with inflammation, metabolism, and heart failure outcomes but not yet examined in the context of obesity and cardiac surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Studies suggest that the increase of serum GDF15 concentration is related to the development and progress of cardiovascular disease (29). The analysis of more than 100 original studies (30)(31)(32)(33)(34) shows that GDF15 has higher value in predicting all-cause mortality in patients with heart failure than traditional cardiovascular risk factors and biomarkers. Other studies have proposed that the expression of GDF15 in the whole nephron is weak in physiological state, but the concentration of plasma GDF15 rises sharply before acute kidney injury (35), scholars believe that it may be an early sign of subclinical kidney injury, but it cannot be detected using conventional clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the increase of serum GDF15 concentration is related to the development and progress of cardiovascular disease (29). The analysis of more than 100 original studies (30)(31)(32)(33)(34) shows that GDF15 has higher value in predicting all-cause mortality in patients with heart failure than traditional cardiovascular risk factors and biomarkers. Other studies have proposed that the expression of GDF15 in the whole nephron is weak in physiological state, but the concentration of plasma GDF15 rises sharply before acute kidney injury (35), scholars believe that it may be an early sign of subclinical kidney injury, but it cannot be detected using conventional clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma NAG-1/GDF15 levels have been reported in human subjects with these diseases [ [16] , [17] , [18] , [19] ] and chronic liver diseases [ 20 , 21 ], suggesting NAG-1/GDF15 may serve as a potential diagnostic biomarker for these diseases. It has been reported that the plasma level of NAG-1/GDF15 was significantly higher in human subjects with obesity or higher body mass index (BMI) [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growth differentiation factor 15 (GDF15), which belongs to the transforming growth factor (TGFB) superfamily [1], is strongly associated with several diseases such as obesity, cancer and cardiovascular diseases as well as with aging [2][3][4]. Under physiological conditions, GDF15 is only weakly expressed in most tissues, whereas pathological states and cellular stress strongly increase GDF15 levels [5][6][7], suggesting it as potential biomarker.…”
Section: Introductionmentioning
confidence: 99%